National Patient Satisfaction Survey as a Predictor for Quality of Care and Quality Improvement – Experience and Practice - Cui J; Du J; Zhang N; Liang Z (Patient Preference and Adherence)
Juan Cui,1,2 Jing Du,2 Ning Zhang,1 Zhanming Liang3 1Affairs Management Office, Shandong Provincial Maternal and Child Health Care Hospital Affiliated to Qingdao University, Jinan, Shandong Province, People’s Republic of China; 2Department of Medical Management, Health Commission of Shandong Province, Jinan, Shandong Province, People’s Republic of China; 3College of Public Health, Medical and Veterinary Sciences, James Cook University, Townsville, Queensland, AustraliaCorrespondence: Ning Zhang, Email zn394114326@126.comBackground: Patient satisfaction is an important predictor of quality of care and hospital services. Patient satisfaction survey provides not only valuable insight into patient experience of care but also evidence that guides quality improvement in both system and organization levels. The paper aims to prove the value of system-wide satisfaction survey of patients and demonstrate whether data collected from a national patient satisfaction survey in three-year period can predict trends in patient experience of care.Methods: Patient satisfaction data of 148 hospitals were extracted from the annual National Public Hospital Patient Satisfaction Survey (NPHPSS) for Shandong Province between 2019 and 2021. Pearson test or Spearman test was performed to clarify the differences in satisfaction and relationship between variables. A linear regression model was established to describe the impact of variables on satisfaction.Results: From 2019 to 2021, there was a significant enhancement in overall patient satisfaction, particularly in communication areas, for both outpatients and inpatients (p = 0.000). A strong and positive correlation between outpatient and inpatient satisfaction was observed over three years (p = 0.000). However, outpatients reported lower satisfaction than inpatients regarding the hospital environment and communication (p < 0.05). Patient care experiences also varied across different hospital categories. In addition, the maturity of the Health Information Management System (HIMS) positively influenced inpatient satisfaction (p < 0.05).Conclusion: A nationwide patient satisfaction survey can predict benefits of quality improvement initiatives and identify changing trends in the quality of hospital care. The strong correlation between outpatient and inpatient satisfaction underscores the importance of consistent medical service quality across the hospitals. HIMS upgrades are a worthwhile investment in enhancing patient experiences in public hospitals. Tailoring service improvement strategies to specific hospital contexts, such as type, location, and patient demographics, is crucial.Keywords: patient satisfaction, quality of care, healthcare information management system, clinician communication